2021
DOI: 10.2217/frd-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Patient-Reported Experience of Living with Wilson Disease

Abstract: Aim: This research was conducted to collect patient-reported data on the experience of living with Wilson disease and to broaden the existing knowledge of a rare neurometabolic disease with varied clinical manifestations. Materials & methods: Adult patients with Wilson disease or caregivers were recruited through a Wilson disease association or advocacy group, and asked to complete an online survey that assessed various aspects of living with Wilson disease. Survey data were analyzed descriptively. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…A comparison study of the effectiveness of prescription zinc acetate and alternative zinc preparations, typically found over-the-counter zinc (zinc salts), implied that both were effective, as the absorption is good in many but not all patients (23). Like our study, the North American survey previously mentioned also found that access to medication was one of the most common concerns for adult patients' future well-being (22). While there are patient assistance programs aimed at increasing access to medication, these are not available to everyone (26).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…A comparison study of the effectiveness of prescription zinc acetate and alternative zinc preparations, typically found over-the-counter zinc (zinc salts), implied that both were effective, as the absorption is good in many but not all patients (23). Like our study, the North American survey previously mentioned also found that access to medication was one of the most common concerns for adult patients' future well-being (22). While there are patient assistance programs aimed at increasing access to medication, these are not available to everyone (26).…”
Section: Discussionsupporting
confidence: 69%
“…The North American survey did not identify emotional burden as a severe issue; however, when this topic was mentioned, the most frequent impacts described were feeling overwhelmed, anxious, or worried and having concerns about the future (22). Our study had similar ndings, with the most commonly reported emotional impacts by patients being feelings of concern about the future, in addition to relief in relation to the diagnosis journey.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The impact of WD on a patient's life was measured using ad hoc questionnaires based on the 5-point Likert scale questions adapted from Dress et al [21], including questions on the difficulty experienced in performing activities of daily living, the impact of the disease on social life, emotional status, and executive function.…”
Section: Research Variables and Instrumentsmentioning
confidence: 99%